Antibacterial and Cytotoxic Compounds from Endophyte Fusarium solani isolated from Centella asiatica (L.). Issue 5 (3rd September 2022) - Moni, Fatema; Saifullah, Naki; Afroz, Farhana; Rony, Satyajit Roy; Sharmin, Suriya; Shahinuzzaman, ADA; Al-Mansur, Muhammad Abdullah; Al-Reza, Sharif Md.; Sohrab, Md. Hossain
Abstract: The antimicrobial and cytotoxic activity of metabolites isolated from an endophyte Fusarium solani were evaluated which was associated with the medicinal plant Centella asiatica Linn. Repeated chromatographic separations of ethyl acetate extract of Fusarium solani lead to the isolation of three naphthoquinone Anhydrofusarubin (1), Fusarubin (2), Javanicin (3) and one aza-anthraquinone 5-deoxybostrycoidin (4). The structures of isolated compounds were determined by analysis of NMR spectrum data and comparison of spectroscopic data with those of known compounds. The cytotoxic activity of isolated compounds was tested against the Human Lung cancer cell line and antimicrobial activity by disc diffusion method. Significant antibacterial activity and Cytotoxicity of the isolated secondary metabolites suggested that Azaanthraquinones and Napthaquinones are potential lead to develop antibacterial and anticancer drugs. GRAPHICAL ABSTRACT: UF0001